2010
DOI: 10.1002/fuce.200900208
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Evaluation of a Fuel Cell–Thermoelectric Generator Hybrid System

Abstract: A hybrid system consisting of a solid oxide fuel cell, a semiconductor thermoelectric generator and a regenerator is put forward. Expressions for the efficiencies and power outputs of the fuel cell, thermoelectric generator and hybrid system are derived. The relation between the electric currents in the fuel cell and thermoelectric generator is revealed. The maximum efficiency and power output of the hybrid system are calculated numerically. The optimally operating electric currents in the fuel cell and thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Min Chen et al [23] used a 3D CFD model to simulate the performance of each thermoelectric module used for heat recovery from 1 kW PEM-fuel cell. Chen et al [24] investigated the performance of a hybrid system which consisted of a solid oxide fuel cell as well as a thermoelectric generator. They presented a correlation between current density of the fuel cell and non-dimension current of thermoelectric modules.…”
Section: Introductionmentioning
confidence: 99%
“…Min Chen et al [23] used a 3D CFD model to simulate the performance of each thermoelectric module used for heat recovery from 1 kW PEM-fuel cell. Chen et al [24] investigated the performance of a hybrid system which consisted of a solid oxide fuel cell as well as a thermoelectric generator. They presented a correlation between current density of the fuel cell and non-dimension current of thermoelectric modules.…”
Section: Introductionmentioning
confidence: 99%
“…3(a) shows that the state of the hybrid system at the maximum power output is different from that of the DCFC or TEG at the maximum power output. It is also observed that the power density of the hybrid system first increases and then decreases as the operating current density is increased, while the efficiency first rapidly decreases then slightly Table 1 Parameters used in the modeling [24,25,37,29,38].…”
Section: Resultsmentioning
confidence: 94%
“…where j = aI g /K and Z = a 2 /(KR) are, respectively, the dimensionless electrical current and the figure of merit of the semiconductor materials [37]. When some heat are transferred from the DCFC DCFC to the TEG, both the power output and the efficiency are larger than zero, i.e., P TEG > 0 and g TEG > 0, and thus one may easily determine the region of the dimensionless electrical current that the TEG takes effect as follows…”
Section: The Tegmentioning
confidence: 99%
“…1, where I f and I g are, respectively, the electric currents flowing through the load resistances R f and R g of the PAFC and TG, T is the working temperature of the PAFC, q 1 andq 2 are, respectively, the heat flows from the PAFC to the TG and from the TG to the environment at temperature T 0 , T 1 and T 2 are the temperatures of the hot and cold junctions of the thermoelectric device, U 1 and U 2 are the overall heat transfer coefficients of heat exchangers at the hot and cold sides of the thermoelectric device, and A 1 and A 2 are the heat transfer areas at the hot and cold sides of the thermoelectric device. By using such a hybrid system, the PAFC acts as the hightemperature heat reservoir of the TG for a further production of power, one part of the waste heat produced in the fuel cell can be availably utilized by the TG operated between T and T 0 , and consequently, the conversion efficiency of the fuel can be enhanced [41]. Below, we will analyze the performance of the PAFC and TG and then synthetically investigate the performance characteristics of the hybrid system.…”
Section: A New Hybrid System Consisting Of a Phosphoric Acid Fuel Celmentioning
confidence: 97%